2021
DOI: 10.3390/ijerph181910237
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Knowledge Gaps and Their Impact on the Role of Pediatricians: A Multicentric Study

Abstract: Purpose: This study aimed to evaluate the current level of pediatricians to promote oral health. In particular, the study sought to determine whether years of experience were associated with the dentistry knowledge of pediatricians. Materials and Methods: Online recruitment was used to obtain a sample of pediatricians from the United States of America, Greece, and Saudi Arabia. These three countries are the participants in this research project. The participants completed an anonymous, online, self-administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Pediatricians should be prepared to give appropriate advice to parents or guardians about first aid for avulsed teeth. They need to have general knowledge of eruption dates and patterns for deciduous and permanent teeth and the difference between a deciduous and a permanent tooth because primary teeth should not be replanted [ 9 , 27 ]. In our study, only 40.3% of the respondents knew that reimplantation of a deciduous tooth is not an option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatricians should be prepared to give appropriate advice to parents or guardians about first aid for avulsed teeth. They need to have general knowledge of eruption dates and patterns for deciduous and permanent teeth and the difference between a deciduous and a permanent tooth because primary teeth should not be replanted [ 9 , 27 ]. In our study, only 40.3% of the respondents knew that reimplantation of a deciduous tooth is not an option.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies and systematic reviews have been conducted to determine the role of medical doctors and pediatricians in children’s oral health and to assess their knowledge, attitudes and professional practice experience. The majority of these studies have shown that physicians and pediatricians have limited knowledge and understanding of critical areas of dentistry, such as oral health and dental trauma management [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Their inadequate knowledge and practice experience result from insufficient education and a lack of oral health content in their educational process and training [ 8 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with many studies nationally and internationally [ 26 , 29 32 ]. A recent multicenter study involving dental pediatricians from three different countries (United States of America, Greece, and Saudi Arabia) found that knowledge was proportionally associated with experience [ 44 ]. Experience was thought to be the reason for the discrepancies seen in oral health-related knowledge and interdisciplinary practices namely referrals [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies documented lack of requisite health knowledge in clinicians [ 35 ], Nepal diabetes patients [ 36 ], paediatricians [ 37 ], Australian pharmacists [ 38 ], health professionals [ 39 ], primary care physicians [ 40 ], and nurses working in heart failure units [ 41 ]. Even worse, the gaps in oral health knowledge among a sample of pediatricians were reported [ 42 ]. Health knowledge deficiency poses a serious threat on the improvement of health conditions among the individuals of interest.…”
Section: Literature Reviewmentioning
confidence: 99%